The Coming Out of Memory: The Holocaust, Homosexuality, and Dealing with the Past - Kurze, Arnaud (Archīum Ateneo, 2024)
This research discusses the challenges of establishing a collective memory for gay victims of the Nazi terror in World War II and examines the introduction of gay victimhood into the public sphere through memorialization efforts. While scholarly accounts on gays and the Holocaust emerged in the 1970s, little is known about the emergence and consolidation of a public narrative on gay persecutions under the Nazis. It raises important questions, including why a public voice for crimes against sexual minorities in World War II emerged only hesitantly? Drawing on historical gay memorialization processes in Germany, the author maps the obstacles for recognition, including external and internal challenges in expanding existing narratives and a collective memory of the past. This fraught advocacy work remains nonetheless crucial to promote commemorations of persecution and discrimination against minority groups that have received limited public acknowledgement.